2022
DOI: 10.31744/einstein_journal/2022ao0149
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with lansoprazole and cholecalciferol is associated with a slower decline in residual beta-cell function and lower insulin requirements in children with recent onset type 1 diabetes: results of a pilot study

Abstract: Objective: To investigate the effects of combination therapy with cholecalciferol and lansoprazole on residual β-cell function and glycemic control in children with new-onset type 1 diabetes. Methods: Children aged 6-12 years with type 1 diabetes were allocated to receive cholecalciferol and lansoprazole (Group 1) or no treatment (Group 2). Children were maintained on their respective insulin regimens and kept records of blood sugar and insulin doses taken. Children were followed at three-month intervals for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…LPZ has been reported to reduce body weight gain, improve glucose tolerance in HFD-fed mice 25 , 26 , ameliorate hepatic steatosis in the hypercholesterolemic rat model 27 , lower circulating glucose in the diabetic gerbil Psammomys obesus 28 , and synergized with antidiabetic medications to improve glycemic control 25 , 29 . Clinical studies have also reported that lansoprazole treatment improved glycemic control in diabetic patients 30 , 31 . However, the molecular mechanism for the metabolic benefits of LPZ remains largely unknown.…”
Section: Discussionmentioning
confidence: 96%
“…LPZ has been reported to reduce body weight gain, improve glucose tolerance in HFD-fed mice 25 , 26 , ameliorate hepatic steatosis in the hypercholesterolemic rat model 27 , lower circulating glucose in the diabetic gerbil Psammomys obesus 28 , and synergized with antidiabetic medications to improve glycemic control 25 , 29 . Clinical studies have also reported that lansoprazole treatment improved glycemic control in diabetic patients 30 , 31 . However, the molecular mechanism for the metabolic benefits of LPZ remains largely unknown.…”
Section: Discussionmentioning
confidence: 96%
“…Another association that has shown promising results on T1D in nonobese diabetic mice and human studies is the combination of dipeptidyl peptidase 4 (DPP-4) inhibitors, gamma-aminobutyric acid, and proton-pump inhibitor (PPI), resulting in long insulin-free periods. 8,9 Reddy et al 10 showed a smaller decline in residual β-cell function and lower insulin requirements in T1D treated with lansoprazole plus cholecalciferol. Verapamil has been shown to delay the progression of T1D for at least 2 years after diagnosis, partially preserved stimulated C-peptide secretion, normalizing the serum levels of chromogranin A (a T1D autoantigen), proinflammatory interleukin-21, and T-follicular-helper cell markers.…”
mentioning
confidence: 99%